Communities in peril global report on health impacts of pesticide use in agriculture. - Dinham, Barbara; Pesticide Action Network (Group). Asia and the Pacific (Penang, Malaysia Pesticide Action Network Asia Pacific, 2010)
This report presents the results of a wide-ranging survey of how pesticides are used in the field by communities around the world. It shows that hazardous pesticides are routinely used in unsafe situations, and supports the call by international agencies for more assertive action on pesticide hazards. The report illustrates the urgent need for significant investment and policy support for agroecological approaches to food, feed and fibre production.
"Edited by: Barbara Dinham from regional reports for PAN International."
Includes bibliographical references (pages 111-116)
In English.
Keywords: Pesticides -- Health aspects; Pesticides -- Environmental aspects